(untitled) (Revista de Investigaciones Universidad del Quindío, 2021)
Family Assets must be defined as the set of rights and obligations that, constituting a legal and economic unit, destined to the satisfaction of the rights of pecuniary content, derived from family coexistence and, where appropriate, to guarantee compliance with These, regardless of the generating cause of the beneficiary primary social group, which may well be marriage, cohabitation, procreation or adoption. Consequently, its legal nature varies, acquiring the characteristics of what modern doctrine calls patrimony affectation, thus expanding the opportunity to allocate other types of assets to the purpose at hand, thus overcoming the traditional possibility of only affecting the house and a cultivable parcel, all types of rights and assets that can be valued in money or susceptible to this type of valuation must be included.